Women writers’ profiles of Soenting Melajoe Newspaper (1912-1921) - Maimon Herawati; Siti Karlinah; Herlina Agustin; Nuryah Asri Sjafirah (Jurnal Kajian Komunikasi, 2022)
Soenting Melajoe Newspaper (1912-1921) was Indonesia’s first indigenous women’s newspaper during the Dutch colonial period. Its readers considered this newspaper as a command in the women’s movement in the Minangkabau society. Editors were deemed as generals, readers as soldiers. The articles in Soenting Melajoe were submitted by women from various regions. The newspaper became a means of exchanging ideas and debating between women, moderated by female editors; Rohana Kudus and Ratna Juwita. This writing constructed the profile of writers based on their writings in Soenting Melajoe. The theory used in this research was the feminist communication theory, focusing on the revalorism aspect of it. This research employed a historical method. Data collection was done through literature study. The subjects of this research are the writings of Indonesian women in Soenting Melajoe. The female writers of Soenting Melajoe came from the administrative center of the Hindia Dutch, port cities, and coffee warehouse regions. Most backgrounds of the writers of Soenting Melajoe were from families of Dutch employees, families managing educational institutions, and families of tribal leaders. Some of the writers of Soenting Melajoe learned to read and write at school. Others studied with family members. Further research can be done on the life of these female writer pioneers and the connection between ideas in Soenting Melajoe and other colonial newspapers.